Herstory in Young Adult Fiction by Joanna Rudniańska Based on the Examples of „Rok Smoka” and „Kotka Brygidy” - Slany, Katarzyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The paper discusses young adult fiction by Joanna Rudniańska, whose works belong to the stream of non-conformist coming-of-age novels marked by experiences of exclusively teenage girls/women, developing in Poland since the 1990s. Both Rok Smoka and Kotka Brygidy emphasise the personal quality of teenage girls and women, and present their fates with a particular consideration of their fairly individualised processes of maturation and intentional development of their identities. The author of this paper employs feminist methodologies to emphasise the ambivalent, borderline, and negative female experiences in the analysed texts. She offers a detailed interpretation of how the protagonists of the above-mentioned novels experience the world; she applies a metaphorical and fantastic perspective of telling herstories, while searching for matrilineal traces, the phenomenon of sisterhood, drastic rituals inscribed in the feminine domain, and the special kind of coming-of-age which constitutes the starting point for personal and subjective herstories.